ETIKA PROFESI KEJAKSAAN DAN TUGAS KOMISI KEJAKSAAN DALAM PENEGAKAN KODE ETIK DAN PENGAWASAN KINERJA JAKSA - Laylatin Khoyrica Aris; Alvi Mafazatus Syauqiyah; Mohammad Hatta (JURNAL ILMIAH NUSANTARA, 2025)
The Prosecutor’s Office is a state institution with the authority to prosecute and a vital role in law enforcement in Indonesia. Based on Law Number 16 of 2004 concerning the Prosecutor’s Office of the Republic of Indonesia, this institution is responsible for upholding law and justice through investigation, prosecution, and execution of court decisions. As a key pillar of the judicial system, the Prosecutor’s Office is required to operate professionally, transparently, and with integrity to maintain public trust in law enforcement institutions. In carrying out their duties, prosecutors must adhere to a code of ethics covering personal ethics, ethics in duty execution, ethics in public service, and ethical interactions with colleagues. This ethical framework is designed to prevent abuse of authority and ensure that prosecutors work in accordance with high legal and moral standards. To ensure compliance with these ethical standards, the Prosecutorial Commission of the Republic of Indonesia plays a crucial role in overseeing prosecutorial performance and enforcing ethical guidelines. The commission is responsible for receiving and addressing public complaints, monitoring prosecutors' conduct, and providing recommendations regarding ethical and disciplinary violations. This study employs a normative juridical approach by analyzing legal regulations related to prosecutorial ethics. Primary data sources consist of various regulations and laws governing the Prosecutor’s Office and its ethical code, while secondary data sources include literature, journals, and relevant books. The findings of this research are expected to provide deeper insights into the implementation of prosecutorial ethics and the role of the Prosecutorial Commission in maintaining prosecutorial professionalism and accountability within Indonesia’s judicial system.